A inserção das tecnologias digitais em prol da educação em tempos de pandemia da Covid-19 - Martins, Paulo Kele Ramos (2020)
The main objective of the article is to present the result of scientific research entitled “The insertion of digital technologies in favor of education in times of the pandemic of the covid-19”, whose general objective is to show that digital technologies are alternative resources that assist in education as Covid-19 pandemic evolutionary teaching medium at CEST / UEA. For the development of the research, the following methodological procedures were used, such as bibliographic survey and field research for the acquisition of information that will show digital technologies as tools that help education in times of pandemic. The research was characterized by a quantitative and qualitative approach, based on Severino (2007), Lakatos (2017), Prodanov (2013, p. 52), Figueiredo (2008, p. 97), Cervo, Bervian and Silva (2007) and Prestes (2007). The questionnaire was used to collect data answered by 8 (eight) academics from CEST-UEA, 1 (one) professor in the Mathematics course at the respective university. After analyzing the data collected in the questionnaires, it was realized that it was possible to see through the responses that digital technologies are innovative resources that help in the search for knowledge in times of Covid-19 pandemic. From the above, we emphasize, therefore, that technology was used to continue classes during the pandemic period, but it is necessary to wait a little longer so that it can be said with absolute certainty that this is the best way to educate in these times where we need to maintain social distance.